P08-21 Neurotoxicity of Octylisothiazolinone (OIT): Evidence from Zebrafish Early-Life Stage - L. Sulcanese; A. Iannetta; T. Silvestrini; G. Angelozzi; V. D'Altilia; S. Zugaro; V. Iezzi; E. Benedetti; M. Perugini (Toxicology Letters, 2025)

Brittle fragmentation of Fissure 17 enclave magma revealed by fractal analysis - V. Haag; B.F. Houghton; D. Perugini; A. Soldati (Journal of Volcanology and Geothermal Research, 2024)

Decarbonation and clast dissolution timescales for short-term magma‑carbonate interactions in the volcanic feeding system and their influence on eruptive dynamics: Insights from experiments at atmospheric pressure - M. Knuever; R. Sulpizio; D. Mele; A. Pisello; A. Costa; D. Perugini; F. Vetere (Chemical Geology, 2023)

Early-life exposure to environmentally relevant concentrations of triclocarban impairs ocular development in zebrafish larvae - Giulia Caioni; Carmine Merola; Cristiano Bertolucci; Tyrone Lucon-Xiccato; Beste Başak Savaşçı; Mara Massimi; Martina Colasante; Giulia Fioravanti; Nunzio Antonio Cacciola; Rodolfo Ippoliti; Michele d’Angelo; Monia Perugini; et al. (Chemosphere, 2023)

The San Gregorio Magno lacustrine basin (Campania, southern Italy): improved characterization of the tephrostratigraphic markers based on trace elements and isotopic data - P. Petrosino; I. Arienzo; F. C. Mazzeo; J. Natale; M. Petrelli; A. Milia; D. Perugini; M. D′Antonio (Journal of Quaternary Science, 2019)
Central–southern Italy is one of the most suitable areas in the world for tephrostratigraphic studies, owing to the numerous volcanic sources with explosive activity during the Pleistocene. This work presents a systematic investigation of the chemical (trace elements) and isotopic (Sr and Nd) compositions of the main tephra markers within lacustrine sediments of the San Gregorio Magno Basin (Campania, southern Italy). This study: (i) provides full geochemical (trace elements and isotopes) characterization of eight significant Upper Pleistocene marker layers (X‐6, X‐5, C‐22, MEGT/Y‐7, CI/Y‐5, C‐10, Y‐3, NYT/C2) widely dispersed over the Mediterranean area; (ii) proposes a new tephra marker for Marine Isotope Stage 7, dated to 240 ka; and (iii) refines the correlations of tephra levels belonging to the investigated sequence. This study highlights that in most cases the Nd isotope composition of the glass and Sr isotope composition of the coexisting minerals are more reliable than 87 Sr/ 86 Sr of the glass, and hence is more helpful as a further tool for tephrostratigraphic correlations, as recently proposed in the literature. Moreover, this study is a first step towards the construction of a complete geochemical database for future tephra investigations in the Mediterranean area. Copyright © 2019 John Wiley & Sons, Ltd.

Phosphorus zoning as a recorder of crystal growth kinetics: application to second-generation olivine in mantle xenoliths from the Cima Volcanic Field - I. Baziotis; P. D. Asimow; T. Ntaflos; J. W. Boyce; F. M. McCubbin; A. Koroneos; D. Perugini; S. Flude; M. Storey; Y. S. Liu; S. Klemme; J. Berndt (Contributions to Mineralogy and Petrology, 2017)

Effect of selective logging on soil organic carbon dynamics in tropical forests in central and western Africa - T. Chiti; L. Perugini; D. Vespertino; R. Valentini (Plant and Soil, 2016)

Experimental constraints on the origin of pahoehoe “cicirara” lavas at Mt. Etna Volcano (Sicily, Italy) - F. Vetere; S. Mollo; P. P. Giacomoni; G. Iezzi; M. Coltorti; C. Ferlito; F. Holtz; D. Perugini; P. Scarlato (Bulletin of Volcanology, 2015)

Time-scales of recent Phlegrean Fields eruptions inferred from the application of a ‘diffusive fractionation’ model of trace elements - Diego Perugini; Giampiero Poli; Maurizio Petrelli; Cristina P. De Campos; D. B. Dingwell (Bulletin of Volcanology, 2010)

Pm37, a new broadly effective powdery mildew resistance gene from Triticum timopheevii - L. D. Perugini; J. P. Murphy; D. Marshall; G. Brown-Guedira (Theoretical and Applied Genetics, 2008)

Influence of landscape morphology and vegetation cover on the sampling of mixed plutonic bodies - D. Perugini; M. Petrelli; G. Poli (Mineralogy and Petrology, 2007)

Time-scales of hybridisation of magmatic enclaves in regular and chaotic flow fields: petrologic and volcanologic implications - M. Petrelli; D. Perugini; G. Poli (Bulletin of Volcanology, 2006)

Insight into the self-association of key enzymes from pathogenic species - Matthew A. Perugini; Michael D. W. Griffin; Brian J. Smith; Lauren E. Webb; Antony J. Davis; Emanuela Handman; Juliet A. Gerrard (European Biophysics Journal, 2005)

Development of viscous fingering between mafic and felsic magmas: evidence from the Terra Nova Intrusive Complex (Antarctica) - D. Perugini; G. Poli; S. Rocchi (Mineralogy and Petrology, 2005)

Magma mixing in the Sithonia Plutonic Complex, Greece: evidence from mafic microgranular enclaves - D. Perugini; G. Poli; G. Christofides; G. Eleftheriadis (Mineralogy and Petrology, 2003)